Very-High-Energy γ-Ray Observations of the Blazar 1ES 2344+514 with VERITAS. Issue 2 (17th July 2017) - Allen, C.; Archambault, S.; Archer, A.; Benbow, W.; Bird, R.; Bourbeau, E.; Brose, R.; Buchovecky, M.; Buckley, J. H.; Bugaev, V.; Cardenzana, J. V; Cerruti, M.; et al.
Abstract: We present very-high-energy γ-ray observations of the BL Lac object 1ES 2344+514 taken by the Very Energetic Radiation Imaging Telescope Array System between 2007 and 2015. 1ES 2344+514 is detected with a statistical significance above the background of 20.8σ in 47.2 h (livetime) of observations, making this the most comprehensive very-high-energy study of 1ES 2344+514 to date. Using these observations, the temporal properties of 1ES 2344+514 are studied on short and long times-scales. We fit a constant-flux model to nightly and seasonally binned light curves and apply a fractional variability test to determine the stability of the source on different time-scales. We reject the constant-flux model for the 2007–2008 and 2014–2015 nightly binned light curves and for the long-term seasonally binned light curve at the >3σ level. The spectra of the time-averaged emission before and after correction for attenuation by the extragalactic background light are obtained. The observed time-averaged spectrum above 200 GeV is satisfactorily fitted (χ 2 /NDF = 7.89/6) by a power-law function with an index Γ = 2.46 ± 0.06stat  ± 0.20sys and extends to at least 8 TeV. The extragalactic-background-light-deabsorbed spectrum is adequately fit (χ 2 /NDF = 6.73/6) by a power-law function with an index Γ = 2.15 ± 0.06stat  ± 0.20sys while an F -test indicates that the power law with an exponential cut-off function provides a marginally better fit (χ 2 /NDF = 2.56/5) at the 2.1σ level. The source location is found to be consistent with the published radio location and its spatial extent is consistent with a point source.